A systematic review of nonpharmacological interventions to reduce procedural anxiety among patients undergoing radiation therapy for cancer - Erin Forbes; Amanda L. Baker; Ben Britton; Kerrie Clover; Eliza Skelton; Lyndell Moore; Tonelle Handley; Sharon Oultram; Christopher Oldmeadow; Alison Gibberd; Kristen McCarter (Cancer Medicine)
Abstract Procedural anxiety is a concern for a number of patients undergoing radiation therapy. While procedural anxiety is often treated pharmacologically, there is a clinical need for effective alternative strategies for patients who are contraindicated from medication use, and those who prefer not to take unnecessary medications. Objectives The primary objective was to assess the efficacy of nonpharmacological interventions delivered to adults with cancer, in the radiation oncology department, just prior to, or during radiation therapy, in reducing levels of self‐reported procedural anxiety. The secondary objectives were to assess the efficacy of these interventions in reducing physiological symptoms of procedural anxiety and anxiety‐related treatment disruptions. Design Systematic review. Data Sources Electronic databases (MEDLINE, CINAHL, EMBASE, PsycINFO and Cochrane Central Register of Controlled Trials) were searched from inception up until February 2022. Inclusion Criteria Population: Adult patients with cancer undergoing external beam radiation therapy. Intervention: Nonpharmacological interventions delivered within the radiation therapy department. Comparison: standard care controls, or standard care plus an alternative intervention. Outcomes: level of self‐reported procedural anxiety (primary), physiological symptoms of anxiety (secondary) and measures of anxiety‐related treatment disruptions (secondary). Data Extraction and Analysis Two reviewers independently extracted data. A meta‐analysis was originally planned but deemed not feasible as the studies could not be confidently pooled for meta‐analysis, due to the variability in the interventions, study designs and the generally low number of studies. Therefore, a narrative synthesis is presented. Results Screening of 2363 records identified nine studies that met inclusion criteria: six studies of music interventions, two of video‐based patient education and one of aromatherapy. Overall, three studies received a global rating of strong methodological quality and low risk of bias. Three studies reported a significant effect of the intervention on reducing the primary outcome of self‐reported procedural anxiety: two music interventions (both strong methodological quality), and one video‐based patient education (moderate methodological quality). One of the studies (a music intervention) also reported a significant reduction in the secondary outcome of physiological symptoms of procedural anxiety (systolic blood pressure). Conclusions The evidence for nonpharmacological interventions delivered to adults with cancer just prior to, or during radiation therapy, in reducing levels of self‐reported procedural anxiety is limited, with very few well‐designed studies. There is a need for interventions for procedural anxiety during radiation therapy to be evaluated through rigorous randomised controlled trials.